Role of Active Inflammatory Mediators in Helicobacter Pylori Associated Chronic Gastritis in Children - o`g`li, Temirov Murodjon Telman (American Journal of Biomedicine and Pharmacy, 2024)
To evaluate the efficacy of triple eradication therapy versus symptomatic therapy in children with Helicobacter pylori–associated chronic active gastritis. The aim of this study was to show whether there is a relationship between fecal calprotectin levels and Helicobacter pylori (H pylori) gastritis in children and to determine the association of fecal calprotectin levels with gastric biopsy results in terms of chronic inflammation and neutrophil activity.